2008
DOI: 10.1002/rcm.3867
|View full text |Cite
|
Sign up to set email alerts
|

Derivatization of sialic acids for stabilization in matrix‐assisted laser desorption/ionization mass spectrometry and concomitant differentiation of α(2 → 3)‐ and α(2 → 6)‐isomers

Abstract: Sialylated carbohydrates usually decompose by loss of sialic acid when ionized by matrix-assisted laser desorption/ionization (MALDI) as the result of the labile carboxylic proton. Stabilization has previously been achieved by forming methyl esters with methyl iodide, a procedure that eliminates the labile proton. In this paper, we describe an alternative procedure for methyl ester formation that provides information on the sialic acid linkage directly from the MALDI spectrum. The sugars were desalted, dissolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
195
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(198 citation statements)
references
References 27 publications
3
195
0
Order By: Relevance
“…Originally, Wheeler et al introduced linkage-speci c methylesteri cation, which is based on di erences in the reactivity of carboxyl groups on sialic acids. 67) Under the derivatization conditions, α2,6-linked sialic acids are converted to esters, whereas α2,3-linked sialic acids form lactones by intramolecular dehydration. e resulting mass di erence obtained from the mass spectra allows the linkage-speci c di erentiation of the types of sialic acids.…”
Section: Linkage-speci C Derivatizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Originally, Wheeler et al introduced linkage-speci c methylesteri cation, which is based on di erences in the reactivity of carboxyl groups on sialic acids. 67) Under the derivatization conditions, α2,6-linked sialic acids are converted to esters, whereas α2,3-linked sialic acids form lactones by intramolecular dehydration. e resulting mass di erence obtained from the mass spectra allows the linkage-speci c di erentiation of the types of sialic acids.…”
Section: Linkage-speci C Derivatizationmentioning
confidence: 99%
“…In fact, Wheeler et al pointed out that lactones can be completely degraded within 50 h by simply dissolving them in water. 67) is instability can limit the downstream chemical and/or enzymatic treatments. 70,71) As pointed out by other researchers, lactone forms cannot survive enzymatic digestion, resulting in partial de-lactonization.…”
Section: Linkage-speci C Derivatizationmentioning
confidence: 99%
“…Sialylated glycans from bovine fetuin and thyroglobulin appeared to lose much less of their sialic acid than when examined with the MALDI-TOF system; spectra were compared with those of stable permethylated samples (spectra not shown). However, even if desialylation is a problem, previous work has shown that sialic acid loss can be prevented by derivatization of the carboxy group of the sialic acids by methyl ester [33,34] or amide formation [35,61] or by selective formation of lactones from α2→3-linked sialic acids [34] with retention of the free hydroxyl groups that are necessary for production of the informative negative ion CID spectra.…”
Section: Positive Ionmentioning
confidence: 99%
“…The spectra of monosialylated glycans, in particular, retain many of the diagnostic ions (data not shown but see reference [64]). However, these glycans can be neutralized by derivatization [33,61], as mentioned above and, in some cases, the derivatization reaction can be exploited to provide linkage information for the sialic acids [34].…”
Section: Negative Ionmentioning
confidence: 99%
See 1 more Smart Citation